The Great Plains, Second Edition - Webb, Walter Prescott (Nebraska, 2022)
Walter Prescott Webb identifies the revolver, barbed wire, and the windmill as technological adaptations that facilitated Anglo conquest of the arid, treeless region of the Great Plains.